C.1 - "Issawi, Charles" (London, 1963)
This book contains following topics: The Background; Integration in the world Economy; Accumulating Difficulties; Arab Socialism; Human Resources; National Income; Agriculture; Industry; Transport and Communications; Foreign Trade and Balance of Payments; Finance; Public Finance; Problems project and Policy.
Keywords: Economics